Respuesta :

Answer:

9/56 is your answer.

Step-by-step explanation:

[7+2(5 - 9)2]/[(4+1)2 - 3(22)=

[7+2(-4)2]/[(5)2-66]=

[7+2(-8)]/[10-66]=

(7+-16)/(-56)=

-9/-56=

9/56 is your answer.

[tex]\bf \cfrac{7+2(5-9)^2}{(4+1)^2-3(2^2)}\implies \cfrac{7+2(\stackrel{\downarrow }{-4})^2}{(\underset{\uparrow }{5})^2-3(\underset{\uparrow }{4})}\implies \cfrac{7+2(\stackrel{\downarrow }{16})}{\underset{\uparrow }{25}-3(4)}\implies \cfrac{7+\stackrel{\downarrow }{32}}{25-\underset{\uparrow }{12}} \\\\\\ \cfrac{39}{13}\implies \cfrac{3}{1}\implies 3[/tex]

recall PEMDAS, parentheses or groups first, from innermost to outermost, then exponents and so on.